The Whilton dispute, 1264-1380 : a social-legal study of dispute settlement in medieval England - Palmer, Robert C., 1947- (Princeton legacy library., 1984)
Robert C. Palmer examines the Whilton dispute, an intrafamilial, multigenerational contest over a large estate that continued, primarily in the courts, from 1264until 1380. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.